The Significance of Qiraat to Legal Istinbat - Dede Suryani; Asep Ahmad Fathurrohman (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the differences in qiraat readings that affect the meaning of legal istinbat. The method used in this research is a qualitative method through literature study by applying content analysis. The results and discussion include general views of qiraat, differences in the variety of qiraat readings, and the meaning of qiraat readings that affect legal istinbat. The conclusion of the study is that qiraat becomes authentic evidence in terms of the meaning of the phenomenon of syara' law that occurs in the midst of Muslims. This research recommends to do a re-examination of other aspects with a more varied approach method.